Census of Population and Housing, 1980 (United States): Special Tabulations of Population 60 Years and Over ([Verlag nicht ermittelbar], 1987)
These data, which correspond to tables provided in the documentation, summarize information on the United States population aged 60 years and over that was collected in the 1980 Census of Population and Housing. The tables were prepared by the Bureau of the Census at the request of the National Institute on Aging. Variables appearing in one or more of the tables are age (in single years or five-year intervals), sex, race (black/white), living arrangements (institutionalization status, household/group quarters, living in families/alone, relationship to householder, persons per room), income (source, personal level, family level, household level, poverty status), veteran status, educational attainment, urban/rural residence, marital status, nativity status, and Spanish origin. In some of the tables totals that exclude amounts allocated for missing data are provided for purposes of comparison. The variables for which non-allocated figures are included are age, race, institutionalization status, income, veterans status, educational attainment, marital status, and Spanish origin. The file contains a complete set of tables for the United States as a whole, for each of the four Census regions, and for each of the 50 States, the District of Columbia, and five territories.